SEMANGAT BUSHIDO ANALISA KULTURAL UNTUK PENGEMBANGAN KARAKTER MASYARAKAT - Siswantara, Yusuf; Mujihandono, Dominicus Subyar (Universitas Katolik Parahyangan, 2021)
Culture and society are two fields of one currency. Both carry inseparable reciprocal consequences. Society produces culture and culture is able to shape society. the character of society determines the culture, but also vice versa, the development of culture will be able to shape the character of the community. Bushido has laid the foundation for the character of Japanese society. These characters are embedded in and shape the younger generation of Japan. This research aims to explore Bushido as a shape for the nation's character with the aim of finding analysis of the model for the development of national character. For that purpose, a library research model is an option in this initial research. The results of this study suggest the cultural side and alternative role models in the development of national character.